Impact of nurse-delivered community-based CD4 services on facilitating pre-ART care in rural South Africa. Issue 1 (December 2016) - Kompala, T.; Moll, A.; Mtungwa, N.; Brooks, R.; Friedland, G.; Shenoi, S.
Abstract Background HIV testing, diagnosis and treatment programs have expanded globally, particularly in resource-limited settings. Diagnosis must be followed by determination of treatment eligibility and referral to care prior to initiation of antiretroviral treatment (ART). However, barriers and delays along these early steps in the treatment cascade may impede successful ART initiation. New strategies are needed to facilitate the treatment cascade. We evaluated the role of on site CD4+ T cell count phlebotomy services by nurses in facilitating pre-ART care in a community-based voluntary counseling and testing program (CBVCT) in rural South Africa. Methods We retrospectively evaluated CBVCT services during five continuous time periods over three years: three periods when a nurse was present on site, and two periods when the nurse was absent. When a nurse was present, CD4 count phlebotomy was performed immediately after HIV testing to determine ART eligibility. When a nurse was absent, patients were referred to their local primary care clinic for CD4 testing. For each period, we determined the proportion of HIV-positive community members who completed CD4 testing, received notification of CD4 count results, as well as the time to test completion and result notification. Results Between 2010 and 2013, 7213 individuals accessed CBVCT services; of these, 620 (8.6 %) individuals were HIV-positive, 205 (33.1 %) were eligible for ART according to South African national CD4 count criteria, and 78 (38.0 % of those eligible) initiated ART. During the periods when a professional nurse was available to provide CD4 phlebotomy services, HIV-positive clients were significantly more likely to complete CD4 testing than during periods when these services were not available (85.5 % vs. 37.3 %, p  < 0.001). Additionally, when nurses were present, individuals were significantly more likely to be notified of CD4 results (60.6 % vs. 26.7 %, p <0.001). The time from HIV screening to CD4 test completion was also significantly shorter during nurse presence than nurse absence (median 8 days (IQR 4–19) vs. 35 days (IQR 15–131), p  < 0.001). Conclusions These findings indicate that in addition to CBVCT, availability of on site CD4 phlebotomy may reduce loss along the pre-ART care cascade and facilitate timely entry into HIV care.